(untitled) (Experimental biology, 2024)
This study aimed to assess the susceptibility of a clinical strain of Bacteroides fragilis (BFR_KZ01) from Kazakhstan, a significant anaerobic pathogen in human infections, to commonly used anti-anaerobic drugs at the local level. Additionally, the research aimed to identify genes with MALDI-TOF/MS associated with antibiotic resistance. To perform surveillance of cfiA-positive Bacteroides fragilis using new subtyping software module, MALDI Biotyper Subtyping Module, on MALDI-TOF MS system, and to evaluate the detection ability of the module.The bacterial isolate was identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and 16S rRNA gene sequencing. Susceptibility to broad-spectrum antibiotics (metronidazole, meropenem, ciprofloxacin, clindamycin, and tetracycline) for intra-abdominal infections treatment was determined. ClinProTools 3.0.22 software was employed to analyze mass spectra groups crucial for identifying cfiA-positive strains. MALDI-TOF/MS analysis classified strain BFR_KZ01 into Group II (cfiA-positive), despite being phenotypically sensitive to meropenem (mean MIC, 1.3 mg/L). The study identified drug resistance determinants in strain BFR_KZ01, demonstrating its multidrug-resistant nature due to carrying nimB, tetQ, and gyrA genes, conferring resistance to metronidazole, tetracycline, and ciprofloxacin.